The hepatocellular model of fatty liver disease: from current imaging diagnostics to innovative proteomics technologies - Hernandez, Renee; Garcia-Rodriguez, Natasha S.; Arriaga, Marco A.; Perez, Ricardo; Bala, Auwal A.; Leandro, Ana C.; Diego, Vince P.; Almeida, Marcio; Parsons, Jason G.; Manusov, Eron G.; Galan, Jacob A. (Frontiers in Medicine, 2025)
Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) is a prevalent chronic liver condition characterized by lipid accumulation and inflammation, often progressing to severe liver damage. We aim to review the pathophysiology, diagnostics, and clinical care of MASLD, and review highlights of advances in proteomic technologies. Recent advances in proteomics technologies have improved the identification of novel biomarkers and therapeutic targets, offering insight into the molecular mechanisms underlying MASLD progression. We focus on the application of mass spectrometry-based proteomics including single cell proteomics, proteogenomics, extracellular vesicle (EV-omics), and exposomics for biomarker discovery, emphasizing the potential of blood-based panels for noninvasive diagnosis and personalized medicine. Future research directions are presented to develop targeted therapies and improve clinical outcomes for MASLD patients.